A simple application of implicit function theorem - Cruz, German Jesus Lozada [UNESP] (My University, 2012)
In this note we show that the roots of a polynomial are C∞ depend of the coefficients. The main tool to show this is the Implicit Function Theorem.

En esta nota se muestra el hecho que las raíces de un polinomio son C∞, depende de los coeficientes. La herramienta principal para mostrar este resultado es el teorema de la funcíon implícita.